Valoración agroecológica de los sistemas de producción caprina en ambientes áridos - Castro, Ornella Eugenia; Gonzalez, Maria Florencia; Herrera, Victor Gaspar; Gómez, Rolando (Sociedad Argentina de Agroecología, 2022)
Póster y ponencia